Does Near-Infrared Spectroscopy Identify Asphyxiated Newborns at Risk of Developing Brain Injury During Hypothermia Treatment? - Peng, Shuo; Boudes, Elodie; Tan, Xianming; Saint-Martin, Christine; Shevell, Michael; Wintermark, Pia (American Journal of Perinatology, 2015)
Objective The aim of this article is to assess whether near-infrared spectroscopy (NIRS) identifies, during hypothermia treatment, the asphyxiated newborns who later develop brain injury.Study Design In this study, asphyxiated newborns, for whom later brain injury was defined by brain imaging and/or autopsy results, were monitored by NIRS during therapeutic hypothermia. We compared regional cerebral oxygenation saturation (rSO2) measured by NIRS at key time points for newborns who developed or did not develop later brain injury.Results A total of 18 asphyxiated newborns treated with hypothermia were enrolled. rSO2 was higher in the asphyxiated newborns who developed later brain injury. Sensitivity within the first 10 hours of hypothermia treatment for an adverse outcome was 100% (95% confidence interval [CI], 70–100%) and specificity was 83% (95% CI, 36–99%).Conclusions NIRS appears to identify asphyxiated newborns at risk of developing brain injury as early as the first 10 hours of hypothermia treatment. Thus, NIRS may have an important role as an early outcome predictor in this population.
Keywords: birth asphyxia; hypoxic-ischemic encephalopathy; magnetic resonance imaging; metabolism; near-infrared spectroscopy; newborn brain; perfusion